PENINGKATAN PENGETAHUAN ANAK PANTI ASUHAN PUTRA UTAMA I MELALUI PENYULUHAN JAJANAN SEHAT PADA ANAK - Marta Halim; Putri Eka Sari; Fitri Savitri (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
The law on health has mandated nutrition improvement efforts to escalate nutritional quality of individuals and communities, including through improving food consumption patterns; improvements of nutrition conscious behavior, improving access and quality of nutrition services in accordance with scientific and technological progress. Community service is carried out at Putra Utama I Orphanage. Problems that occur 70% of children at the Orphanage have a lack of knowledge about healthy snacks. It also does not have its own canteen for children to buy snacks and there has never been counseling about healthy snacks. The purpose of community service activities is to increase the knowledge of Putra Utama I Orphanage Children’s. The method was counseling about healthy snacks and giving pretest and posttest questionnaires to know their knowledge about healthy snacks. The results obtained are an increase in the average knowledge score of the Orphanage children’s in pretest and posttest was 14.9043. It can be concluded that counseling at Orphanage children can increase knowledge about healthy snacks.